2020
DOI: 10.1016/j.celrep.2020.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Regulatory Strategies of NF-κB RelA Target Genes in the Inflammatory Response Reveals Differential Transactivation Logics

Abstract: Ngo et al. developed a genetic complementation system for NF-kB RelA that reveals that NF-kB target-gene selection requires high-affinity RelA binding and transcriptional activation domains for gene induction. The synergistic and redundant functions of two transactivation domains define proinflammatory and inflammation-response genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 70 publications
(81 reference statements)
2
37
0
Order By: Relevance
“…To further dissect the molecular mechanism of RELA FUS -driven ependymoma formation, we examined the implication of RELA target genes in the RELA FUS1 transcription network using publicly available Rela ChIP-seq data in murine embryonic fibroblasts (MEFs) after TNF stimulation [ 37 ]. We found that approximately 22% of RELA FUS1 peaks in mEPN cells overlapped with Rela peaks in MEFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further dissect the molecular mechanism of RELA FUS -driven ependymoma formation, we examined the implication of RELA target genes in the RELA FUS1 transcription network using publicly available Rela ChIP-seq data in murine embryonic fibroblasts (MEFs) after TNF stimulation [ 37 ]. We found that approximately 22% of RELA FUS1 peaks in mEPN cells overlapped with Rela peaks in MEFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the canonical NF-κB consensus motif, termed as κB site (5′-GGGRNWYYCC-3′, R = A or G, N = any base, W = A or T, and Y = C or T) was not present among the top 10 motifs in either RELA FUS1 or RELA FUS1−S486E peaks (Additional file 11 : Table S3A) [ 5 , 24 , 36 ]. In turn, when applying the TF motif analysis to Rela Peaks in MEFs [ 37 ], the NF-κB-like motif (5′-KGGAAADYCCM-3′, K = G or T, D = A or G or T, M = A or C) was identified in only 17.4% of the Rela target genes as the most enriched motif, thus confirming the presence of Rela binding on non-NF-κB consensus sequence (Additional file 4 : Fig. S3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-COV-2 virus mainly targets respiratory epithelial cells, alveolar epithelial cells, vascular endothelial cells and pulmonary macrophages, all of which express Angiotensin converting enzyme 2 (ACE2) receptor, triggering the generation of pro- inflammatory cytokines and chemokines (including IL-6, TNF, IL-10 and MCP1) 41 . The NF-kB family member RELA is a widely expressed and effective transcriptional activator that activates the expression of many inflammatory through exposure to pathogens and inflammatory cytokines 42 . RELA may play an important role in the infection of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that for some cells the promoters of NF-κB-dependent genes are primed in cis to respond rapidly to the increase in NF-κB abundance, for example, through higher accessibility or the pre-loading of poised polymerase. Of note, recent genome-wide analysis of NF-κB-mediated nascent transcription in mouse embryonic fibroblasts revealed a class of very early genes (including TNF ), with nascent transcripts peaking as early as 15 min post stimulation ( Ngo et al., 2020 )—earlier than the peak in NF-κB nuclear concentration. Detailed ChIP analysis at the promoters of these genes might therefore shed light on the nature of first responders.…”
Section: Discussionmentioning
confidence: 99%